Direct Current Drive with Observer - Rinkevičienė, R.; Petrovas, A. (Elektronika ir Elektrotechnika, 2008)
Design of direct current drive with reduced order observer, applied for estimation of armature current is analyzed. Current is controlled by relay controller with histeresis loop. This method allows avoiding of controllable direct current voltage source. The system requires to measure just one output signal – motor speed. Due to this reason electric drive has simple, cheep and safe construction. Comprehensive analysis of state variable feedback vector design is presented. Simulink model of the drive is elaborated. Step responses of motor speed and armature current are presented and analyzed. Ill. 5, bibl. 6 (in English; summaries in English, Russian and Lithuanian).